THE ROLE OF MOTIVATION IN MEDIATING EFFECT OF EXPECTATION TO ATTITUDE - Anugerah, Desy Gistya; Noermijati, Noermijati (Jurnal Aplikasi Manajemen, 2018)
This study aims at finding out the relationship between expectation and motivation on tourist attitude towards tourism destination. The expectation and motivation are expected to affect visitor's satisfaction, happiness, enjoyment, worthiness, and attractiveness. This research used primary data collected using a survey technique from the Museum Angkut visitor. The collected data were processed using path analysis. The findings of this study show that expectation and motivation have a significant influence on the visitor Attitude towards Museum Angkut. Moreover, the result also shows another role of motivation in the relationship between expectation and attitude. Thus, to maintain tourist attitudes towards the tourism destination, motivation and expectation should be considered as one of the critical elements. Further research should explore more about the three variables are taken.